Increasing use of antibiotics in pregnancy during the period 2000–2010: prevalence, timing, category, and demographics. (23rd April 2014) - Broe, A; Pottegård, A; Lamont, RF; Jørgensen, JS; Damkier, P
<x xml:space="preserve">Abstract</x> Objective The aim of this study was to describe the use of antibiotics in a national population‐based cohort of pregnant Danish women between 2000 and 2010. Design Register‐based, population‐wide, cohort study. Setting Denmark, from 2000 to 2010. Population All pregnancies among Danish residents during the period 2000–2010 were included for analysis. Methods Data were obtained from the Danish Medical Birth Registry, the Danish National Patient Registry, and the Registry of Medicinal Product Statistics. The filled prescriptions for systemic antibacterial, antimycotic, and antiviral drugs, as well as intravaginally applied antibiotics, were analysed. Associations with demographic variables were assessed using multivariate analysis. Main outcome measures Filled prescriptions for antibiotic drugs during pregnancy. Results We included 987 973 pregnancies in Denmark from 2000 to 2010; 38.9% of women with a delivery and 14.8% of women with a miscarriage or termination of pregnancy had one or more antibiotic treatments during pregnancy. Systemic antibacterial drugs were the most frequently used drug group, with filled prescriptions for 33.4% of all deliveries and 12.6% of all abortions. This proportion increased from 28.4% in 2000 to 37.0% in 2010 among deliveries. The biggest change was seen for pivmecillinam, which increased among deliveries from 6.3% in 2000 to 19.5% in 2010. Obese (odds ratio 1.51; 95% CI 1.47–1.56), young (odds ratio 1.35; 95% CI 1.30–1.39), and low‐educated women (odds ratio 1.37; 95% CI 1.35–1.1.39) tended to fill more prescriptions of antibiotics during pregnancy. Conclusions Overall, the number of women who filled prescriptions of antibiotics increased during the 11‐year study period. In 2010, at least 41.5% of all deliveries were exposed to antibiotic therapy during pregnancy.